Waterborne poly(urethane-urea) gas permeation membranes for CO2/CH4 separation - Reis, Rodrigo A.; Pereira, Juliana H. C.; Campos, Antoniel C. C.; Barboza, Elaine M.; Delpech, Marcia C.; Cesar, Deborah V.; Dahmouche, Karim; Bandeira, Cirlene F. [UNESP] (Wiley, 2018)
In this work, dense membranes from aqueous dispersions of poly(urethane-urea) (PUU) based on poly(propylene glycol) (PPG) and a block copolymer composed of poly(ethylene glycol) (PEG) and poly(propylene glycol) (PPG), EG-b-PG, with 7 wt % of the former were obtained. Nonpolluting formulations were synthesized with proportions of PPG and EG-b-PG as 1:0, 1:1, 1:3, and 3:1 in terms of equivalent number ratios. The effect of small and gradual increases in PEG segments was evaluated for the permeability of pure CO2, CH4, and N2, at room temperature. Slight increases in PEG-based segments in PUU promoted some remarkable properties, which led to a simultaneous increase in CO2 permeability and ideal selectivity for CH4 (300%) and N2 (380%). Infrared spectroscopy showed that the PEG portions induced hydrogen bonds between NH of urethane and ether groups in the PEG portions, which promoted ordering of the flexible segments, confirmed by X-ray diffractometry and small-angle X-ray scattering. Diffractometry techniques also confirmed the absence of crystalline domains, as did dynamic mechanical analysis. The produced membranes showed performance above Robeson's 2008 upper bound and seemed to be a superior polymeric material for CO2/CH4 and CO2/N2 separation. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2018, 135, 46003.
Keywords: membranes; oil and gas; polyurethane; structure–property relationships